2010
DOI: 10.1113/expphysiol.2010.054189
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity alters signalling pathways and induces atrophy and apoptosis in skeletal muscle in a prediabetic rat model

Abstract: Pro-inflammatory and stress-activated signalling pathways are important role players in the pathogenesis of obesity and insulin resistance. Obesity and type II diabetes are associated with chronic, low-grade inflammation and elevated tumour necrosis factor-α (TNF-α) levels. There is increasing evidence that TNF-α may play a critical role in skeletal muscle atrophy. However, the effects of obesity-induced insulin resistance on these signalling pathways are poorly understood in skeletal muscle. Therefore, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
119
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 55 publications
11
119
1
Order By: Relevance
“…However, findings are more inconsistent when studying muscle atrophy and fiber size in high fat diet-induced obesity models. Sishi and colleagues found that 16 weeks of Western diet resulted in decreased fiber CSA in rats [6]. Shortreed et al [35] however, reported increased fiber CSA in soleus muscle after 8 weeks of 60% fat diet.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, findings are more inconsistent when studying muscle atrophy and fiber size in high fat diet-induced obesity models. Sishi and colleagues found that 16 weeks of Western diet resulted in decreased fiber CSA in rats [6]. Shortreed et al [35] however, reported increased fiber CSA in soleus muscle after 8 weeks of 60% fat diet.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to inhibiting insulin signaling, obesity and/or HF diet can have detrimental effects on skeletal muscle structure and function, including fibrosis, atrophy associated with reductions in myofiber cross sectional area and total muscle mass, decreased strength, and impaired regeneration in response to injury [6][7][8]. Fibrosis is the excessive accumulation of matrix proteins, and collagen is the most abundant protein deposited in tissue in response to injury [9].…”
Section: Introductionmentioning
confidence: 98%
“…While up-regulation of MAFbx and MuRF-1 was demonstrated in experimental models of food deprivation, over feeding has also been reported to affect their expression [87].…”
Section: Nutritional Factorsmentioning
confidence: 98%
“…Macrophage infiltration has also been demonstrated by a number of groups (Hevener et al 2007, Fink et al 2014, but not all (Tam et al 2012), to be a feature of obesity-associated IR in skeletal muscle, and a synergistic interaction between macrophages and fatty acids that leads to impaired muscle insulin action has been reported (Varma et al 2009). However, an alternative proposal is that dyslipidaemia associated with obesity activates cellular stress signalling pathways and thereby apoptosis and atrophy in skeletal muscle (Sishi et al 2011). In particular, SFA can specifically induce pro-inflammatory macrophage activation and consequent p38 MAPK-mediated IR in cultured myotubes, an effect that is ameliorated by the UFA palmitoleate (Talbot et al 2014).…”
mentioning
confidence: 99%